PENGARUH PENAMBAHAN a-TOKOFEROL PADA MEDIA PENGENCER TRIS KUNING TELUR TERHADAP KUALITAS SEMEN CAIR DOMBA GARUT - herdis, herdis; kusuma, ida; D, i wayan Angga (Badan Pengkajian dan Penerapan Teknologi, 2009)
The study was conducted to know the influence of a- tocoferrol additional into the egg yolk tris extender medium to the liquid semen quality of “Garut” lamb (Ovis aries). Parameter which had been evaluated i.e. percentages of progressive motile sperm, percentages of viable sperm and percentages of plasma membrane. On the 4 th day evaluation showed that the addition of a- tocoferrol with the dose 0,04 g/100 ml into the egg yolk tris extender produced the highest percentages ofprogressive motile sperm, percentages of viable sperm and percentages of plasma membrane ( 49,0 ± 6,5%; 68,6 ± 4,2% and 59,3 ± 6,5% ) but there were not significantly different from control ( 45,5 ± 5%; 66,0 ± 4,6% and 56,2 ± 5,7% )and the addition of a- tocoferrol with the dose 0,02 g/100 ml ( 49,0 ± 6,5%; 66,6 ± 4,0% and 59,3 ± 2,8% ) respectively. In conclusion, the addition of a-tocoferrol in the egg yolk tris extender medium no significant effect on the liquid semen quality.